Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Siswa Kelas IV SD Negeri Ketaren Tahun Pembelajaran 2023/2024 - Ester Julinda Simarmata; Cristin Monica Siburian; Cristin Monica Siburian; Dyan Wulan Sari HS (Journal on Education, 2024)
Based on the discussion of this research, the researcher outlines the conclusions and suggestions prepared based on all research activities regarding the influence of the Mind Mapping learning model on the learning outcomes of class IV students at SD Negeri 047159 Ketaren for the 2023/2024 academic year as follows: This research uses the Mind Mapping learning model to improve results studying fourth grade students at SD Negeri 047159 Ketaren. On the first day of the research, the researcher gave a pretest of 30 questions to determine the students' initial abilities. The pretest results showed an average score of 53.5, with 1 student who completed and 31 students who did not, this score did not meet the completion requirements based on the KKM score. After that, the researcher provided treatment using the Mind Mapping learning model during the learning process. Then, the researchers tested the students again by giving a posttest of 30 questions to evaluate the effect of the treatment given. The posttest results showed an increase in the average score to 81.5, with 30 students who completed and 2 students who did not. The final step, researchers gave a Mind Mapping model questionnaire to students with an average score of 83.75. The research results show that there is a significant influence of the Mind Mapping learning model on the learning outcomes of class IV students at SD Negeri 047159 Ketaren. This can be seen from the increase in the average pretest score of 53.5 to the average posttest score of 81.5. Based on the results of hypothesis testing, the Ha hypothesis is accepted and the Ho hypothesis is rejected. The use of the Mind Mapping learning model has proven effective in improving the learning outcomes of class IV students at SD Negeri 047159 Ketaren. The average student score experienced a significant increase after implementing this model.